Web-Based Information System for Sales Data and Transaction Reports at Gubug Alit MSMES - Fadly Nur Al Ghifari; Pusaka Ampuh Adikuasa; Muhammad Nashrul Husaini (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Information systems play an important role in improving efficiency and accuracy in data management, especially for Micro, Small, and Medium Enterprises (MSMEs). Gubug Alit MSME still uses a manual recording system for managing sales data and transaction reports, which may lead to recording errors, data loss, and delays in report preparation. This study aims to design and develop a web-based sales data and transaction reporting information system to support more effective and efficient financial management. The methods used include system requirements analysis, system design, and implementation using the Laravel framework with a MySQL database. The result of this study is an information system equipped with user authentication, dashboard, category management, budgeting, transaction recording, and financial reporting features that can be exported into PDF and Excel formats. This system improves the speed, accuracy, and convenience of managing sales data and generating transaction reports at Gubug Alit MSME.